Estimating Cost-Effectiveness in Type 2 Diabetes: The Impact of Treatment Guidelines and Therapy Duration. (July 2015) - McEwan, Phil; Gordon, Jason; Evans, Marc; Ward, Thomas; Bennett, Hayley; Bergenheim, Klas
Objectives . Type 2 diabetes mellitus (T2DM) clinical guidelines focus on optimizing glucose control, with therapy escalation classically initiated within a "failure-based" regimen. Within many diabetes models, HbA1c therapy escalation thresholds play a pivotal role, controlling duration of therapy and, consequently, incremental costs and benefits. The objective of this study was to assess the relationship between therapy escalation threshold and time to therapy escalation on predicted cost-effectiveness of T2DM treatments.Methods . This study used the Cardiff Diabetes Model to illustrate the relationship between costs and health outcomes associated with first-, second-, and third-line therapy as a function of time on each. Data from routine clinical practice were used to contrast predicted costs and health outcomes associated with guideline therapy escalation thresholds compared with clinical practice. The impact of baseline HbA1c and therapy escalation thresholds on cost-effectiveness was investigated, comparing a sodium/glucose cotransporter 2 inhibitor v. sulfonylurea added to metformin monotherapy.Results . Lower thresholds are associated with a shorter time spent on monotherapy, ranging from 1.1 years (escalation at 6.5%) to 13 years (escalation at 9.0%) and an increase in total lifetime cost of therapy. Treatment-related disutility is minimized with higher thresholds because progression to insulin is delayed. Using metformin combined with either dapagliflozin or a sulfonylurea to illustrate lower baseline HbA1c and/or higher therapy escalation thresholds was associated with increased cost-effectiveness ratios, driven by a longer duration of therapy.Discussion . A marked difference in treatment cost-effectiveness was demonstrated when comparing routine clinical practice with guideline-advocated therapy escalation. This is important to both health care professionals and the wider health economic community with respect to understanding the true cost-effectiveness profile of any particular T2DM therapy option.